The impact of the soluble epoxide hydrolase cascade on periodontal tissues - Abdalla, Henrique Ballassini; Van Dyke, Thomas E. (Frontiers in Dental Medicine, 2023)
Periodontitis is a chronic inflammatory disease with complex pathogenesis. Uncontrolled inflammation is driven by the immune system in response to accumulation of oral biofilm that leads to alveolar bone loss, bleeding, increased periodontal probing depth with loss of attachment of the connective tissues to the tooth, and ultimately, tooth loss. Soluble epoxide hydrolase (sEH) is an enzyme that converts epoxy fatty acids (EpFAs) produced by cytochrome P450 (CYP450) to an inactive diol. It has been shown that EpFAs display important features to counteract an exaggerated inflammatory process. Based upon this observation, inhibitors of sEH have been developed and are being proposed as a strategy to regulate proinflammatory inflammatory lipid mediator production and the chronicity of inflammation. This mini review focuses on the impact of sEH inhibition on periodontal tissues focusing on the mechanisms involved. The interaction between Specialized Pro-Resolving Mediators and sEH inhibition emerges as a significant mechanism of action of sEH inhibitors that was not formerly appreciated and provides new insight into the role SPMs may play in prevention and treatment of periodontitis.